Are Seasonal Anomalies Real? A Ninety-Year Perspective - Lakonishok, Josef; Smidt, Seymour (Review of Financial Studies, 1988)
This study uses 90 years of daily data on the Dow Jones Industrial Average to test for the existence of persistent seasonal patterns in the rates of return. Methodological issues regarding seasonality tests are considered. We find evidence of persistently anomalous returns around the turn of the week, around the turn of the month, around the turn of the year, and around holidays.